2014
DOI: 10.1179/1743132814y.0000000451
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a microcatheter-based selective intra-arterial hypothermia on hemodynamic changes following transient cerebral ischemia

Abstract: Cold saline, when infused directly into the ischemic brain region, can confer robust neuroprotection by reducing immediate post-ischemic hyperperfusion and delayed post-ischemic hypoperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…In our experiments we observed an order of magnitude reduction in infarct volume. Infarct volume reductions ranging from 30% to 90% for short duration localized cold fluid infusions have been reported, with the greatest benefits associated with infusions that were initiated before or as close to reperfusion as possible 24 26 27. These benefits were observed over a range of studied target temperatures (30.5–35°C) and treatment durations as short as 5 min but not exceeding 1 hour.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our experiments we observed an order of magnitude reduction in infarct volume. Infarct volume reductions ranging from 30% to 90% for short duration localized cold fluid infusions have been reported, with the greatest benefits associated with infusions that were initiated before or as close to reperfusion as possible 24 26 27. These benefits were observed over a range of studied target temperatures (30.5–35°C) and treatment durations as short as 5 min but not exceeding 1 hour.…”
Section: Discussionmentioning
confidence: 97%
“…We have shown that localized brain tissue cooling can be quickly and safely achieved with cold saline delivered through an insulated catheter. To date, preclinical models of cold saline infusions have been explored in rodent and non-human primate models 24–27. We sought to demonstrate in a large animal model of temporary MCA occlusion with endovascular occlusion of the MCA (eg, no craniotomy with potential artificial augmentation of localised cooling) effective focal cooling that reduces infarct volume.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our aim was to investigate the safety and efficacy of cold saline administration early after bleeding started. We used an established intracarotid saline infusion method for rats (Chen et al , 2015 ). We hypothesized that while focal cooling may mitigate injury and edema, cooling and use of heparinized saline may induce coagulopathy, thereby worsening outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This "luxury reperfusion" has been implicated in post-reperfusion edema formation, the primary cause of death within 1 month of ischemic stroke [45,46]. While hypothermia prevents intracranial-pressure elevations by itself, LEVI provides an additional protective mechanism by washing out vasodilatory metabolites built up during the ischemic period, which minimizes the extent of hyperperfusion-related injury [29,47]. As evidence of this mechanism, fast warm (37°C)-saline LEVI has been shown to signiicantly reduce infarct volumes and improve functional recoveries compared to systemic infusion of warm saline [28].…”
Section: Metabolite Washout and Atenuated Hyper-or Hypoperfusionmentioning
confidence: 99%